Minimal changes in heart rate of incubating American Oystercatchers (Haematopus palliatus) in response to human activity. (30th July 2014) - Borneman, Tracy E.; Rose, Eli T.; Simons, Theodore R.
Abstract: An organism's heart rate is commonly used as an indicator of physiological stress due to environmental stimuli. We used heart rate to monitor the physiological response of American Oystercatchers ( Haematopus palliatus ) to human activity in their nesting environment. We placed artificial eggs with embedded microphones in 42 oystercatcher nests to record the heart rate of incubating oystercatchers continuously for up to 27 days. We used continuous video and audio recordings collected simultaneously at the nests to relate physiological response of birds (heart rate) to various types of human activity. We observed military and civilian aircraft, off-road vehicles, and pedestrians around nests. With the exception of high-speed, low-altitude military overflights, we found little evidence that oystercatcher heart rates were influenced by most types of human activity. The low-altitude flights were the only human activity to significantly increase average heart rates of incubating oystercatchers (12% above baseline). Although statistically significant, we do not consider the increase in heart rate during high-speed, low-altitude military overflights to be of biological significance. This noninvasive technique may be appropriate for other studies of stress in nesting birds.